Understanding The Process Of Strategic Change From A Structurational And Cognitive Perspective: Case Study Of The Users Of A New Technology - Slocum, Alesia (Cranfield University, 2007)
How does strategic change happen, and how is it understood around technology? This ethnographic research has sought to better understand this process, from a structurational, cognitive and practice perspective. Researchers have shown that change is a continuous and ongoing process (Tsoukas and Chia, 2002; Weick and Quinn, 1999), while others have shown that change, while not determinate, can be intentional and directed to a large extent by change agents in practice (Balogun and Johnson, 2004; Whittington, 1992, 2006; Pettigrew, 1992; Johnson, 1990; Jarzabkowski, 2003). On a more macro level, Giddens has shown that the process of social organising, or structuration, happens through iterative and recursive production and reproduction of structure through communicated action (Giddens, 1979, 1984) which many authors have gone on to research in relation to technological change (Orlikowski, 1992, 1996, 2000; Barley, 1986; Pozzebon and Pinsonneault, 2002; Walsham, 2002, Heracleous and Barrett, 2001). However, it is also known that much to do with change happens cognitively, where the participants in change must reinterpret and adapt their mental frameworks to adjust to something new. (Huff and Huff, 2000; Davidson, 2006; Kaplan and Tripsas, 2005; Balogun and Johnson, 2004). This research seeks to align these concepts, by starting from the notion that continuous, iterative and recursive change in practice can be intentionally directed on a cognitive level. It then further explores the role that the cognitive activities of change recipients, and organisational structures such as technology, play in this process. Specifically, this research has explored a case where strategic change was made to occur in the context of a new technology implementation. It is grounded in a longitudinal, qualitative, practice based case study which followed the implementation of a Sales Force Automation system. Change was examined under a structurational lens and then operationalised through the identification of schemata. The study looks at how the new technology was perceived and used over time by participants in the change programme as it progressed. It is presented in narrative form, where a Literature Review and Methodology comprise Project I of the DBA, and the First and Second Order Analyses comprise Projects II and III. Data have been based principally upon 42 recorded interviews with 14 people gathered over 2½ years during 4 different time periods. The analysis is also supplemented with information from surveys, statistics on the technology and its usage, and contextual information that was collected by the author, who was employed at the company during the period studied and managed the global technology project. All of the change recipients interviewed were sales people with separate sales territories—they interacted more with the technology, with customers, and with other parts of the business, than with each other, and they were given relative flexibility regarding whether, when and where to use the new system. This study has explored the notion that schemata can consist of both perceived structures and mental actions, implying that they are structurational dualities held cognitively. It is then argued that the dualities held by the change recipients, over time, were themselves juxtaposed, and that it was this iterative and recursive mental juxtaposition that was a fundamental step in creating a strategic change process. Additionally, the analysis proposes that there were some basic measures taken in the course of strategically changing the individual and group schemata in Logico that can be seen differently under a cognitive and structurational lens, including the definition of time and episodes and the manner in which attention was focused on the new system. Finally, the study explores the phenomena in this case from a perspective of Strategy as Practice, by taking a holistic view of some of the practices, praxis, and practitioners involved in this strategic change. Understanding this cognitive and recursive process better can help organisations to manage strategic change in a way that works with changing mental frameworks and contextual situations over time. It also contributes to our knowledge of how strategic outcomes are iteratively shaped by the adopters of new technology when deliberate strategising initiatives take the form of technological innovation.